2015
DOI: 10.1002/asia.201500611
|View full text |Cite
|
Sign up to set email alerts
|

Facile and Divergent Synthesis of Lamellarins and Lactam‐Containing Derivatives with Improved Drug Likeness and Biological Activities

Abstract: With the goal to improve the aqueous solubility of lamellarins, the lactone ring in their skeleton was replaced with a lactam moiety in azalamellarins. However, the reported synthetic route produced such derivatives in very low yields. Hence, this study focused on developing an efficient simplified total synthetic scheme that could furnish both azalamellarins and the parent lamellarins from the same pyrrole ester intermediates. Subsequent comparative profiling revealed that the introduced lactone-to-lactam rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 59 publications
1
15
0
Order By: Relevance
“…Most reported syntheses of the pentacyclic lamellarins proceed via precursors or intermediates already possessing a suitably functionalized pyrrole core onto which the additional rings are elaborated . Less commonly, the pyrrole ring is created by cyclization involving condensation or cycloaddition between an isoquinoline precursor and moieties that supply either the C-1/C-2/C-3 or the C-2/C-3 components of the targets . Even rarer are approaches in which the pyrrole ring is formed by the attachment of a building block that provides only C-3, with most or all of the lamellarin’s carbon framework already in place .…”
Section: Resultsmentioning
confidence: 99%
“…Most reported syntheses of the pentacyclic lamellarins proceed via precursors or intermediates already possessing a suitably functionalized pyrrole core onto which the additional rings are elaborated . Less commonly, the pyrrole ring is created by cyclization involving condensation or cycloaddition between an isoquinoline precursor and moieties that supply either the C-1/C-2/C-3 or the C-2/C-3 components of the targets . Even rarer are approaches in which the pyrrole ring is formed by the attachment of a building block that provides only C-3, with most or all of the lamellarin’s carbon framework already in place .…”
Section: Resultsmentioning
confidence: 99%
“…1/1000 of common tertiary amines). In contrast to the highly lipophilic parental lamellarins, 40 these ammonium salts were highly soluble in water. For example, the estimated solubilities of 14b and 14f in water were 19 mg/mL and 41 mg/mL, respectively, as determined by a HPLC method ( The guanidinium group can recognize carboxylate anions by exceptionally potent ionic and hydrogen bonding interactions.…”
Section: Synthesismentioning
confidence: 91%
“…Synthetic analogues related to the polyandrocarpamines 955 were found to be inhibitors of H 2 S production by cystathionine beta-synthase, 956 and SAR studies have been reported for thiaplidiaquinones A and B 957 (various biological targets), 958 cadiolides A-C 959,960 (antibacterial), 961,962 rubrolides 963 (photosynthesis inhibitors), 964 meridianins 965 (antimalarial and antituberculosis), 966 isogranulatimide 967 (cytotoxicity), 968 and lamellarins 969 (cytotoxicity). 970…”
Section: Molluscsmentioning
confidence: 99%